Acidman [videorecording (DVD)] - Dowling, Chris; Lehmann, Alex; Agron, Dianna; Church, Thomas Haden; Luqmaan-harris, Sameerah (Brainstorm Media, 2024)
Maggie tracks down her estranged father Lloyd, now living in the Oregon wilderness obsessed with UFOs; together they attempt to make first contact.